TRACKER SYSTEM SINGLE AXIS SOLAR CONCENTRATOR IN 2 W SUN HEAT POWER PLANT - Ananda Eddy Irvine; Sujono Sujono; Akhmad Musafa (MAESTRO, 2023)
This paper discusses the single-axis solar concentrator tracker system for solar thermal power plants. This system concentrates the harvesting of heat from solar radiation to increase the electrical power generated from the solar thermal conversion process. The solar concentrator is designed as a parabola and can adjust the direction following the sun's motion. The overall system work is regulated by Arduino Mega 2560. A 24-volt DC motor and BTS7690 driver are used to drive the parabola. RTC DS3231 is used to provide real-time data. ACS712 sensor is used to measure the current and voltage generated. The conversion of solar heat into electrical energy is done using Peltier SP1848. All generated data is recorded to the SD Card module, which will later be used to analyze the overall system performance. The tracker system is designed to move following the sun’s position, starting from 08:00 at position 19O to 17:00 at position 139O. Update the position or direction of the parabola to 15O, done every hour. The effectiveness of the tracker is assessed by comparing the solar concentrator system that is not equipped with a tracker. From the tests conducted for two consecutive days, the tracker-equipped solar concentrator system produced an average percent increase in electrical power of 4.86% on the first day and 5.26% on the second day. The average percent increase in power for two days was 5.06%. The results show that the application of the tracker is able to increase the productivity of the solar thermal power generation system. This opens up opportunities for larger-scale deployment in solar concentrator farms.